If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 7x + 15 = 15 + -3x Reorder the terms: 15 + 7x = 15 + -3x Add '-15' to each side of the equation. 15 + -15 + 7x = 15 + -15 + -3x Combine like terms: 15 + -15 = 0 0 + 7x = 15 + -15 + -3x 7x = 15 + -15 + -3x Combine like terms: 15 + -15 = 0 7x = 0 + -3x 7x = -3x Solving 7x = -3x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '3x' to each side of the equation. 7x + 3x = -3x + 3x Combine like terms: 7x + 3x = 10x 10x = -3x + 3x Combine like terms: -3x + 3x = 0 10x = 0 Divide each side by '10'. x = 0.0 Simplifying x = 0.0
| (16/x^2)*(x^2/24) | | -11=-5x | | x/6-8=-14 | | 2=6x-3y | | 2x+10=3x+15 | | 4(x+3)+1=5(2x-3)-(x+2) | | 5x=-11 | | 8x+5y=28 | | log(3)5x=log(3)160 | | 29=-3+4x | | 13=-6w | | 8(x)/7+9+30 | | 9*u+7=5(u+3) | | 6(w+1)=2*w+34 | | 6x(6+4x)=26+x | | -8*v-2=-6(v-1) | | .125D-3(D-7)=5.125D-3 | | 21=-7*u+4(u+6) | | x^2-xy+3x^2+4xy= | | 2(v-7)+5*v=28 | | (x+1)(x-2)/x+3 | | 2(x+4)+3*x=-12 | | 7*y+23=4*y+8*y-22 | | x/5-12=4 | | -8=5x+3 | | k(2)-25=0 | | 2y+3=(y+21) | | 6*y+5=8*y+11 | | 28+19*x=-8+15*x | | 6x+8=11-4c | | -83=2*v-15*v-18 | | x+x+6x=119+6x |